(3GdJhMOs (3cja CSGYO GHfj GdeUGH HGdJhMO ?s - (3YHO GdeMSf, QjgGes; (3ShGM, SGde YHO GdeYRs; (3UdGM, eQhIs ((3GdefhajI, eUQs (3MhGOjJ ddfTQ hGdJhRjYs, 2024)
(3GSCd faSc HGSJeQGQ gPg GdCSFdI GdegeI(B: (3gd eG CbQCg GdBf ef GdeMJed Cf jchf efGSHG dWadj? gd gj eYdheGJ LOjOI? gd SJSGYO?gd ef eUOQ ehKhb? eGgh eBd gPG GdGVWQGH hGdeSJbHd? cja CNJGQ GdHQfGeL GdYdGLj GdefGSH dWadj? eGgh JGKjQ GdGVWQGH Ydj GdCNhI(B: (3ZjQI ef GdGgJeGe HCNjge Ce YGQ ef hLhOg CeGe CUMGHge Ce GVWQGQ ddYRdI Ce JMed eSFhdjJg? cjajI GdJYGed eY Sdhcg GdeVWQH? gd SCage Wadj jheG eG?gd jYGfj Wadj ef UYhHI aj Gdfhe NdGd Gddjd ChGdCcd?gd SjJcde Ch jJYde?s
Keywords: (3GdJhMOs -- (3CeQGVs; (3GdUMI GdfaSjIs